The burden of blood-pressure-related cardiovascular mortality in Mexico - Cortés Hernández, Dora Elia; Lundelin, Krista J.; Picazzo Palencia, Esteban; Cruz, Juan J. de la; Sánchez, José J.; Banegas, José R. (2014)
This study shows that in Mexico, a country at an advanced stage in the epidemiologic transition, with the national burden of disease dominated by noncommunicable diseases, elevated blood pressure is a major clinical and public health problem. 31.7% of the Mexican individuals aged 50 and over had systolic hypertension, and 47.3% were at systolic prehypertensive levels. Also, approximately half of all cardiovascular deaths that occurred annually in the population of Mexico aged ≥50 years are attributable to above optimal levels of systolic blood pressure. We think these estimates may help order health priorities in Mexico (and other middle-income countries) at a time when the costs of medical care take a considerable share of the gross national product in most countries.